Natural Products Research in China From 2015 to 2016 - Liu, Haishan; Zhu, Guoliang; Fan, Yaqin; Du, Yuqi; Lan, Mengmeng; Xu, Yibo; Zhu, Weiming (Frontiers in Chemistry, 2018)
This review covers the literature published by Chinese chemists from 2015 to 2016 on natural products (NPs), with 1,985 citations referring to 6,944 new compounds isolated from marine or terrestrial microorganisms, plants, and animals. The emphasis is on 730 new compounds with a novel skeleton or/and significant bioactivity, together with their source organism and country of origin.